2021
DOI: 10.1080/21681805.2021.1900387
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk for renal cell carcinoma in end stage renal disease – a population-based case-control study

Abstract: Purpose: End-stage renal disease (ESRD) is a known risk factor for the development of renal cell carcinoma (RCC). This case-control study was performed to assess the risk in a nationwide cohort and evaluate tumor characteristics and survival in the ESRD-RCC population. Methods: In this study, 9,299 patients with RCC identified in the National Swedish Kidney Cancer Register from 2005 until 2014 and 93,895 matched controls were linked to the Swedish Renal Registry and the National Patient Register. ESRD was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Since the underlying immunologic dysfunction of CKD is related with RCC risk [ 13 ] [ 67 ], the influenza vaccination–induced immunomodulation might explain its possible protective effects. Dialysis patients had a several-fold increase in the prevalence of RCC, regardless of the underlying cause [ 68–70 ]. We found that dialysis patients with influenza vaccination had a lower risk of RCC than those who were unvaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…Since the underlying immunologic dysfunction of CKD is related with RCC risk [ 13 ] [ 67 ], the influenza vaccination–induced immunomodulation might explain its possible protective effects. Dialysis patients had a several-fold increase in the prevalence of RCC, regardless of the underlying cause [ 68–70 ]. We found that dialysis patients with influenza vaccination had a lower risk of RCC than those who were unvaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…ESRD is a global health burden, with an overall prevalence of 823 patients per million population [11] . In addition, ESRD is associated with a higher risk of cardiovascular disease and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that around 2–7 % of patients with ESRD develop RCC and this risk with time. RCC in ESRD patients presents predominantly as small, low-stage and low-grade tumors [11] . Due to this increased risk, many providers have opted to perform regular screening for patients with ESRD on dialysis, although guidelines describing the optimal imaging modality (ultrasound vs. CT vs. MRI), screening intervals, and target population have yet to be established [19] , [20] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auf der anderen Seite ist bekannt, dass eine chronische terminale Niereninsuffizienz, die sich durchaus bei nicht oder inadäquat behandelter NLUTD entwickeln kann, das Risiko der Entstehung eines Nierenzellkarzinoms erhöht. In einer landesweiten populationsbasierten Fall-Kontroll-Studie aus Schweden [64] hatten Patienten mit einer terminalen Niereninsuffizienz ein etwa 4,5-fach erhöhtes Risiko (OR 4,5; 95%- KI 3,6), abhängig von der Dauer der terminalen Niereninsuffizienz: Nach weniger als 9 Jahren betrug die OR 2,9 (95%-KI 2,2-3,9), nach mehr als -Jahren betrug die OR 10,2 (95%-KI 7,0-14,8).…”
Section: Andere Urologische Malignome Bei Neurologischen Erkrankungenunclassified